Competitiveness of the Russian Federation in the Global Tourism Market - Bucher, Slavomir (Economy of Regions, 2016)
At present, the tourist industry is one of the fastest growing economic branches of the global economy. For many countries, it brings a significant portion of revenues to their national economies. In the article, the identification and assessment of the secondary data of the World Economic Forum published in The Travel & Tourism Competitiveness Report are carried out. In the Report, the strengths and weaknesses of some countries in the international tourist market are specified in detail. The plan of the analysis is in a more precise specification of competitiveness indices, which consist of compound indices: I - legal framework; II - business environment and infrastructure; III - human, cultural and natural resources for the Russian Federation and some states of Post-Soviet geopolitical space. The goals of the paper are the evaluation of the 14 factors that affect destination competitiveness and the comparison of the competitiveness levels in the Russian Federation. The paper also aimed to provide an understanding of the Russian position in the international tourism market and provide suggestions in order to improve weaknesses of the country. The competitiveness ranking 2015 for the tourism infrastructure, prioritization of travel and tourism, and national tourism perceptions suggest that Estonia, Latvia, Lithuania and Russia rank the top, relative to other former Soviet Union countries in the sample. Since these countries outperform in a tourism infrastructure, it is likely that they continuously try to improve their physical and financial infrastructure for tourists in the country. Therefore, it is a great challenge for Russia to constantly monitoring new trends and occurrences in the international tourism market, which are more diverse needs and demands of the tourist clientele. The findings of this study also shed light on the competitiveness of the Russian Federation operating in the international tourism market. As understood from the findings, there still exists a large gap between the Russian Federation and especially the top ten leaders in terms of tourism competitiveness.